INTEGRATING LOCAL CULTURE INTO EOP COURSES: PERCEPTIONS OF PRESCHOOL EDUCATION MAJORS IN A CHINESE VOCATIONAL COLLEGE - Ren , Xiaoqin; Soekarno, Megawati (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2026)
As higher education institutions increasingly prioritise English for Occupational Purposes (EOP) to enhance internationalisation and equip students for specific professional roles, ensuring curriculum alignment with students' career needs becomes paramount. For preschool education major students, this necessitates mastering English proficiency tailored to kindergarten bilingual teaching contexts. Despite growing emphasis on EOP in higher education, limited research has examined how local cultural integration within hybrid project-based learning (HPBL) frameworks can enhance communicative competence among preschool education majors. This study employs needs analysis to investigate how integrating local culture within a hybrid project-based learning (HPBL) framework can address identified learner needs and enhance communicative competence. The study begins with a needs analysis to identify the specific linguistic, social, and cultural challenges learners face in real-world communication. Based on these findings, the pedagogical approach is developed by embedding culturally relevant content into project tasks, thereby increasing learner engagement and contextual relevance. These tasks are delivered through a hybrid project-based learning model, which combines face-to-face interaction with digital collaboration to create a flexible and supportive learning environment. Through this process, learners are guided to complete projects that require meaningful communication and cultural reflection. A qualitative needs analysis was conducted using open-ended questionnaires administered to 20 second-year preschool education majors. Data was analysed using inductive thematic analysis. Findings reveal strong learner support for integrating local folklore, classroom discourse practices, and culturally grounded teaching materials. However, existing curricula remain predominantly exam-oriented and linguistically focused, with minimal contextualisation to kindergarten teaching scenarios. The study contributes to EOP curriculum design by proposing a culturally responsive HPBL model that aligns vocational language training with localised pedagogical realities.